THE USE OF TECHNOLOGICAL TOOLS IN TEACHING AND LEARNING ENGLISH AS A FOREIGN LANGUAGE FOR JUNIOR HIGH SCHOOL - Tampubolon, Hotma Udur; Said, Mashadi; Saragih, Gustaman (Universitas Indraprasta PGRI, 2024)
This research explores the use of Information and Communication Technology (ICT) in teaching English as a Foreign Language (EFL) at Yadika Junior High Schools in Bekasi. It aims to identify the ICT tools used by teachers and students, assess the benefits of ICT integration, and examine the challenges encountered. Using a qualitative methodology, content analysis, and a thematic approach based on Miles and Huberman's model, the study analyzes data from Yadika 8 Jatimulya, Yadika 11 Jatirangga, and Yadika 13 Tambun. Findings show extensive use of ICT tools like laptops, projectors, smartphones, Google Classroom, and YouTube. ICT boosts student engagement, supports language skill development, and introduces innovative teaching methods. However, challenges include limited technology access, insufficient teacher digital competence, and time constraints for preparing ICT-based materials. The study concludes that successful ICT integration requires ongoing teacher development, better infrastructure, and strategic curriculum design to enhance EFL education.Keywords: ICT, EFL, ICT tools, student engagement, ICT integration challenges